1990
DOI: 10.1007/bf01410672
|View full text |Cite
|
Sign up to set email alerts
|

Use of porous biodegradable polymer implants in meniscus reconstruction. 1) Preparation of porous biodegradable polyurethanes for the reconstruction of meniscus lesions

Abstract: Porous biodegradable poly(urethanes) for reconstruci~ng menisci have been prepared using two different combinations of techniques: freeze-drying/salt-leaching and in-situ polymerization/salt-leaching. Using these methods, homogenous porous materials with a controllable and reproducible morphology can be prepared. The materials were made of three different poly(urethanes): a methylenediphenyldiisocyanatebased polyurethane, a lysine diisocyanate-based poly(urethane), and a poly(e-caprolactone)-based poly(urethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…It has been found that optimal ingrowth of fibrocartilagenous tissue takes place if the pore size is in the range of 200-300 µm [18]. Therefore the scaffold should contain a maximal number of pores in that range, consequently as much sugar as possible should be mixed with the polymer solution.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been found that optimal ingrowth of fibrocartilagenous tissue takes place if the pore size is in the range of 200-300 µm [18]. Therefore the scaffold should contain a maximal number of pores in that range, consequently as much sugar as possible should be mixed with the polymer solution.…”
Section: Resultsmentioning
confidence: 99%
“…There the foams had a similar size of the large pores in combination with a major amount of micro pores that could not be infiltrated with cells. Moreover, the interconnectivity was determined by the size and number of the micro pores [18]. A decrease in small pores in combination with a constant overall porosity and an increase in interconnectivity will increase the volume suitable for cell ingrowth and cell viability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations